Correlation between Ferritin Levels with Malondialdehyde and Neutrophil Lymphocyte Ratio on Iron Overload - Imam Budiwiyono; Purwanto AP; Nyoman Suci Widyastiti; Hadian Hadian; Kusmiyati DK (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Thalassemia major is one of the types of thalassemia that need a routine blood transfusion. If not treated immediately, the patient will only last for 1-8 months. Blood transfusions performed at least or more than 10 times causes iron overload. Excess levels of Fe ions in the body will be stored in the form of ferritin. If the ferritin level is high, cell damage will occur in the presence of a fat peroxidation reaction or Malondialdehyde (MDA). Cell damage can trigger proinflammation, which increases neutrophil counts and decreases lymphocyte counts. The Neutrophil-Lymphocyte Ratio (NLR), which measures the ratio between Absolute Neutrophil Count (ANC) divided by Absolute Lymphocyte Count (ALC) with a manual peripheral blood picture. This study aimed to determine the correlation of ferritin levels with MDA and NLR in iron overload. This study used an analytical observational design with a cross-sectional approach, with samples were thalassemia patients who received repeated blood transfusions at the General Hospital Dr. R Soetrasno, Rembang City and Regional General Hospital Dr. R Soedjati, Grobogan Purwodadi. Inclusion criteria were age 10-18 years, transfusion 10-20 times, normal body temperature. Exclusion criteria were Fe therapy orally, leukocytosis, chronic kidney disease. In the MDA levels, there was no significant difference where p=0.25 by Spearman test. In the NLR there was no significant difference where p=0.91 by Spearman test. There is no correlation between ferritin levels with MDA and NLR in iron overload.